Micro thermo - elastic homogeneous mixtures - Chanh, Trương Minh (Vietnam Journal of Mechanics, 1982)
The present work is concerned with the construction of a linear theory of thermo - elasticity for micro - homogeneous solid mixtures. The constitutive equations of those solids are obtained and the thermodynamic restrictions are studied.